Solve the following differential equation (3 marks)
d
2
y
dx2
− 6
dy
dx + 9y = x
2
e
3x
using the method of undetermined coefficients.
Solve the correspondent homogeneous differential equation.
The characteristic equation for this differential equation and its roots are
"r_{1,2}=3"
The complementary solution is then
Find the particular solution of the non-homogeneous differential equation
Then
"+e^{3x}(4Ax^3+3Bx^2+2Cx)"
"+e^{3x}(12Ax^3+9Bx^2+6Cx)"
"+e^{3x}(12Ax^3+9Bx^2+6Cx)"
"+e^{3x}(12Ax^2+6Bx+2C)"
Substitute
"+e^{3x}(24Ax^3+18Bx^2+12Cx)"
"+e^{3x}(12Ax^2+6Bx+2C)"
"-e^{3x}(18Ax^4+18Bx^3+18Cx^2)"
"-e^{3x}(24Ax^3+18Bx^2+12Cx)"
"+e^{3x}(9Ax^4+9Bx^3+9Cx^2)"
"=x^2e^{3x}"
"x^4: 9A-18A+9A=0"
"x^3: 9B+24A-18B-24A+9B=0"
"x^2: 9C+18B+12A-18C-18B+9C=1"
"=>A=\\dfrac{1}{12}"
"x^1: 12C+6B-12C=0=>B=0"
"x^0: 2C=0=>C=0"
The general solution of the given differential equation is
Comments
Leave a comment